Analisis e-WOM Newsjacking Arei Outdoor pada Konten Viral Surat Keberatan Eiger Adventure - Jasmine Alya Pramesthi (Program Studi Ilmu Komunikasi, 2022)
The social media was enlivened by Eiger's objection letter to content uploaded by YouTubers regarding Eiger product reviews. Eiger's competitor, Arei, used this viral case to create compensation letter content for the public who wanted to review Arei's products. This was considered a smart move to get public attention, known as newsjacking. This had led to many responses by netizens and caused electronic Word of Mouth (e-WOM). This study was conducted to analyze the e-WOM in Arei Outdoor Newsjacking contents. The results of this study suggested that through dimensions of intensity, positive valance of opinion, negative valance of opinion, and content, it was discovered that there were various netizen responses, both positive and negative. This research recommended the importance of further studies on how far newsjacking can build consumer loyalty towards a product